2022
DOI: 10.1186/s12886-022-02571-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the neutrophil-to-lymphocyte ratio and diabetic retinopathy in adults from the United States: results from the National Health and nutrition examination survey

Abstract: Background Diabetic retinopathy (DR) is a common complication of diabetes mellitus (DM). Systemic inflammation is intimately associated with DR. The neutrophil-to-lymphocyte ratio (NLR) index is a relatively new indicator of inflammation. Methods This cross-sectional study was carried out among adults with DM based on the National Health and Nutrition Examination Survey (NHANES) from 2009 to 2016. NLR was presented as absolute neutrophil counts/ ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…The differences may be related to the methodology of research and classification of DR but also patients’ age, BMI, comorbidities, and geographical and ethnic differences. Moreover, the relationship between NLR and DR appears to be non-linear [ 49 ], and some studies have suggested that changes in NLR and PLR may be more informative when analyzed as continuous variables rather than categorical variables based on arbitrary cut-off values [ 2 , 50 , 51 ]. T2DM patients often present with a unique but diverse series of risk factors, comorbidities, and complications, which may accumulate over time due to an inappropriate lifestyle [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences may be related to the methodology of research and classification of DR but also patients’ age, BMI, comorbidities, and geographical and ethnic differences. Moreover, the relationship between NLR and DR appears to be non-linear [ 49 ], and some studies have suggested that changes in NLR and PLR may be more informative when analyzed as continuous variables rather than categorical variables based on arbitrary cut-off values [ 2 , 50 , 51 ]. T2DM patients often present with a unique but diverse series of risk factors, comorbidities, and complications, which may accumulate over time due to an inappropriate lifestyle [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Li et al identified an elevated NLR as a dependable marker for diabetic retinopathy [ 26 ]. In a multivariate analysis conducted by He et al in 2022, the NLR was related to the risk of diabetic retinopathy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, the increased infiltration of neutrophils and heightened adhesion between neutrophils and the endothelium result in retinal inflammation and vessel leukostasis, contributing to the progression of DR [ 3 ]. To date, studies have confirmed a positive correlation between diabetic retinopathy and both the neutrophil-to-lymphocyte ratio (NLR) and the neutrophil percentage-to-albumin ratio (NAR) in peripheral blood [ 4 ]. NETosis is a specific cell death process of neutrophils [ 5 ] and is characterized by the release of neutrophil extracellular traps (NETs), which are extracellular structures composed of chromatin and proteins such as myeloperoxidase (MPO), citrullinated histone H3 (Cit-H3), and neutrophil elastase (NE) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%